A pesquisa em psicologia: ensaio sobre a Psicologia enquanto ciência, a pesquisa qualitativa e o uso da entrevista como principal instrumento de coleta de dados - Camargo, Mário Lázaro [UNESP]; Correr, Rinaldo (My University, 2011)
For constituting itself a science, Psychology has coursed along way. From the time he was considered a Philosophy’s discipline until to be recognized as a legitimate science, Psychology had to devoteto the definition of its object of study, the development and refinement of theoretical-methodological frameworks and, in particular, to consolidation process of their research strategies and knowledge construction. Therefore, in order to regard the demands of the classical scientific paradigm, which is very influenced by Positivism, Psychology made use, initially, of quantitative methodology and laboratory research. This article presents some of the process of identity construction of Psychology as a science, focusing on its transition path between the quantitativist paradigm of scientific knowledge production to the qualitativist paradigm, until that is more commonly practiced nowadays: the collaborative use of these methodological strategies. For presenting the qualitative researching Psychology, we discussed, beyond its proposal and differentiation elements in relation to quantitative research, the different methods used for this mode and, in particular, the interview - which is considered the main way of data collection in surveys conducted by psychologists and, therefore, it is an important element the process of knowledge building that science, in addition to being the most qualified space for dialogue between there searcher and the research subject.

Para se constituir ciência, a Psicologia percorreu um longo trajeto. Desde o tempo em que fora considerada disciplina da Filosofia até ser reconhecida como ciência legítima, a Psicologia teve que se dedicar à definição de seu objeto de estudo, ao desenvolvimento e refinamento de referenciais teórico-metodológicos e, em especial, a um processo de consolidação de suas estratégias de pesquisa e construção de conhecimento. Por isso, e para atender às demandas do clássico paradigma científico, muito influenciado pelo positivismo, a Psicologia serviu-se, inicialmente, da metodologia quantitativa e da pesquisa laboratorial. Este artigo apresenta um pouco do processo de construção da identidade da Psicologia enquanto ciência enfocando sua trajetória de transição entre o paradigma quantitativista de produção do conhecimento científico para o paradigma qualitativista, até chegarmos ao que hoje se pratica de forma mais comum: a utilização colaborativa das duas estratégias metodológicas. Para apresentar a pesquisa qualitativa em Psicologia, discutimos, além de sua proposta e elementos de diferenciação em relação à pesquisa quantitativa, os diferentes métodos utilizados por esta modalidade e, em especial, a entrevista; considerada a principal forma de coleta de dados em pesquisas conduzidas por psicólogos e, portanto, importante elemento no processo de construção do conhecimento dessa ciência, além de mais qualificado espaço de diálogo entre o sujeito pesquisador e o sujeito pesquisado.
Research inpsychology: essay on psychology as a science, qualitative research and the useof the interviews the main instrumentfor data collection
Keywords: Psychology; Qualitative research; Quantitative research; Methods; Interview; Psicologia; Pesquisa qualitativa; Pesquisa quantitativa; Método; Entrevista